Mechanisms of Cisplatin-Induced Acute Kidney Injury: The Role of NRF2 in Mitochondrial Dysfunction and Metabolic Reprogramming - Jihan Liu; Yiming Wang; Panshuang Qiao; Yi Ying; Simei Lin; Feng Lu; Cai Gao; Min Li; Baoxue Yang; Hong Zhou (Antioxidants)
Cisplatin (Cis) is a widely used chemotherapy drug, but its nephrotoxicity limits its clinical application. Acute kidney injury (AKI) is a common complication, restricting long-term use. This study investigates the mechanisms of cisplatin-induced AKI and explores potential therapeutic targets. C57BL/6J mice were intraperitoneally injected with 20 mg/kg cisplatin to establish an AKI model. Serum creatinine, urea nitrogen, and tubular injury biomarkers (NGAL, KIM-1) progressively increased, indicating kidney dysfunction. Mitochondrial ATP levels significantly decreased, along with reduced mitochondrial fission and fusion, suggesting mitochondrial dysfunction. Increased oxidases and reduced antioxidants indicated redox imbalance, and metabolic reprogramming was observed, with lipid deposition, impaired fatty acid oxidation (FAO), and enhanced glycolysis in proximal tubular epithelial cells (PTECs). Nuclear factor erythroid 2-related factor 2 (NRF2) is a key transcriptional regulator of redox homeostasis and mitochondrial function. We found NRF2 levels increased early in AKI, followed by a decrease in vivo and in vitro, suggesting activation in the stress response. Nfe2l2 knockout mice showed aggravated kidney injury, characterized by worsened kidney function and histopathological damage. Mechanistically, Nfe2l2 knockout resulted in redox imbalance, reduced ATP synthesis, mitochondrial dysfunction and metabolic dysregulation. Furthermore, we activated NRF2 using dimethyl fumarate (DMF), observing a reduction in kidney damage and lipid deposition in mice. In conclusion, activating NRF2-dependent antioxidant pathways plays a crucial role in protecting against cisplatin-induced AKI. NRF2 may serve as a potential target for developing therapeutic strategies to prevent cisplatin nephrotoxicity.